Analisis Tingkat Kinerja Penanaman Modal Dalam Negeri Dan Penanaman Modal Asing Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2000-2014 - Sarwiono, Ganjar (2016)
Economic growth is a matter of the economy in the long term and is influenced by various factors. This study aimed to analyze the effect of domestic investment, foreign investmen, labor and goverment expenditure to economic growth in indonesia. The analytical method used was Ordinary Least Square (OLS). For purpose of analysis used secondary data from the 2000-2014 time series that Indonesian GDP data, the value realization of domestic investment, foreign investment realizable value, the number of people 15 years and over who worked in the main job opportunities in Indonesia, and the data government spending. The data obtained from the Central Bureau of Statistics, the Investment Coordinating Board, and other sources, namely journals and research. The results showed the variables of Labour and Government Spending, together positive and significant impact on economic growth in Indonesia by the coefficient value of 0.581928 and 0.239241. While the study variables Domestic Investment (DCI) and Foreign Direct Investment (FDI), jointly and no significant negative effect on economic growth in Indonesia with coefficient of -0.001217 and 0.012289